Manajemen Sumber Daya Insani - Sukarno L. Hasyim (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2019)
Human Resource Management is needed to improve the effectiveness of human resources in the organization. The aim is to provide an effective work unit organization. To achieve this goal, the study of personnel management will show how companies should obtain, develop, use, evaluate, and maintain employees in the right quantity (quantity) and type (quality). There are various models for solving problems in human resource management. The determination of the settlement model is adjusted to the size of the company. This Human Resource Management not only relies on management functions such as planning, organizing, directing and controlling, but on its implementation also relies on the operational functions of HR management, such as recruitment, selection, performance appraisal, training and development, and the practice of compensation. The Islamic viewpoint, this also does not experience differences. All Human Resource management practices are carried out as well as possible, based on what is already in the Qur'an and Al-Hadith.